Periodontal health literacy in Germany - Results of a telephone survey - Deinzer, Renate; Jordan, Andreas Rainer; Justus Liebig University Giessen (My University, 2024)
Background: The prevalence of periodontitis is high. One explanation for this may be that people lack periodontal health literacy (PHL). Methods: This was a cross-sectional descriptive study. Former participants of the 5th German Oral Health Study (n = 333 16-year-olds, n = 307 39–48-year-olds, n = 332 69–78-year-olds) participated in a computer-assisted telephone interview. Open-ended questions (OEQs) were used to assess the participants' current knowledge. Corresponding single- and multiple-choice questions (SCQs and MCQs) supplemented the OEQs to allow detailed analyses of the nature of the knowledge gaps. Results: Less than 10% of the participants in the three age groups could explain the term ‘periodontitis’ or select the correct answer in an SCQ. Responding to the OEQs, 89% of 16-year olds, 64% of 39-48-year-olds, and 59% of 69–78-year-olds, could not name any consequence of periodontitis, and 83%, 51%, and 60%, respectively, could not name any risk factors. The OEQs regarding proper oral hygiene behaviour revealed that participants lacked awareness regarding important aspects of oral hygiene (e.g., systematics) or areas to which they should pay attention to (e.g., interdental spaces and gingival margins). Conclusions: The survey revealed PHL deficits in German adolescents, adults, and seniors and a need for community-based measures to improve PHL in all age groups. Dental teams should be aware that their patients might lack the PHL necessary for understanding and adherence to professional dental advice, and that they might even lack PHL regarding the proper use of oral hygiene devices.
Keywords: ddc:610